Literature Study on the Implementation of Professional Ethics in General Medical Practice - A. Fadilah Nur Rizqi; Mutiara Dwi Lathifahtul Ulyaa (Nusantara Sehat: Jurnal Kesehatan Indonesia, 2025)
ABSTRACT This study aims to analyze the implementation of professional ethics in general medical practice through a comprehensive qualitative literature review. The primary objective is to identify how ethical principles are understood, applied, and institutionalized in the daily practices of medical professionals. Using a qualitative-descriptive approach, data were collected from scholarly books, peer-reviewed journal articles, and official reports published between 2015 and 2025. The analysis employed thematic synthesis, involving processes of identifying, categorizing, and interpreting recurring themes related to ethical behavior, education, and professional culture. The results reveal that the effective implementation of professional ethics depends on three interrelated dimensions: ethical education, organizational support, and contextual adaptation to medical challenges. Ethics education enhances practitioners’ moral sensitivity and judgment, while institutional commitment—through transparent leadership and reflective culture—strengthens ethical accountability. Moreover, the rise of digital technology and global health challenges, such as telemedicine and pandemic response, requires ongoing adaptation of ethical frameworks. The study concludes that professional ethics in medicine is a dynamic construct shaped by both individual reflection and systemic reinforcement. Its contribution lies in integrating theoretical and practical insights that promote the development of ethically resilient and socially responsive healthcare systems. Keywords: professional ethics, general medical practice, ethical competence, qualitative study, medical professionalism.